Introduction to industrial polypropylene : properties, catalysts, processes - Malpass, Dennis B.; Band, Elliot I. (John Wiley & Sons, 2012)
This introductory text is an important resource for new engineers, chemists, students, and chemical industry personnel to understand the technical aspects of polypropylene which is the 2nd largest synthetics polymer in manufactured output. The book considers the following topics: What are the principal types of polypropylene and how do they differ? What catalysts are used to produce polypropylene and how do they function? What is the role of cocatalysts and how have they evolved over the years? How are industrial polypropylene catalysts tested and the resultant polymer evaluated?